2007
DOI: 10.1111/j.1872-034x.2007.00052.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus reduces the therapeutic effectiveness of interferon‐α2b plus ribavirin therapy in patients with chronic hepatitis C

Abstract: The findings indicate that DM reduces the response to IFN-alpha2b plus ribavirin therapy in CHC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…These adipocytokines lead to IFN resistance by blocking STAT phosphorylation. Recent data indicate that the incidence of altered baseline glucose level and the appearance of diabetes type 2 were greater in non-responder cases than in SVR cases [14] . Experimental data obtained by using the replicon model also reported that when insulin levels similar to those seen in patients in a hyperinsulinemic state were added to IFN, the ability to block HCV replication disappeared [15] .…”
Section: Discussionmentioning
confidence: 99%
“…These adipocytokines lead to IFN resistance by blocking STAT phosphorylation. Recent data indicate that the incidence of altered baseline glucose level and the appearance of diabetes type 2 were greater in non-responder cases than in SVR cases [14] . Experimental data obtained by using the replicon model also reported that when insulin levels similar to those seen in patients in a hyperinsulinemic state were added to IFN, the ability to block HCV replication disappeared [15] .…”
Section: Discussionmentioning
confidence: 99%
“…While knowledge of disease and treatment outcome in diabetic HCV patients will have wide clinical applicability, those patients have historically been excluded from clinical trials. There is, however, early evidence of a central role for insulin resistance (IR), a fundamental finding in type 2 DM, in failure to achieve SVR in HCV patients [12][13][14][15][16][17][18]. In a prospective study of Spanish patients with chronic hepatitis C (CHC) [16], SVR was only 32.8% in HCV genotype 1 patients with IR (defined by the homeostasis model of assessment, HOMA-IR [ 2) compared to an SVR rate of 60.5% in those with without IR (HOMA-IR B 2).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, identifying patients who are at risk of developing diabetes, and have CHC, reduces liver disturbance progression [267,268] , the incidence of HCC and transplant-related morbidity and mortality. Additionally, this identification improves the response to antiviral therapy [269][270][271] , even reducing the side effects of the treatment [270] by encouraging the pretreatment of IR and DM [265] . Moreover, clinical trials on HCV-positive patients have reported improvement in glucose metabolism after antiviral treatment [187] .…”
Section: Prevention and Treatmentmentioning
confidence: 99%